The Multiple Impact of Pulau cinta Tourism Object on the Community's Economy in Teluk Kenidai Village, Kampar District, Riau Province - Fathia Azizi; Darwis AN; Trisla Warningsih (Faculty of Fisheries and Marine, Universitas Riau, 2023)
The research was carried out in Pulau Cinta, Teluk Kenidai Village, Tambang District, Kampar Regency, Riau Province. This study aims to identify the type of business, and the economic impact of the Pulau Cinta tourist attraction on the people's economy, and analyze the multiple impact value of the Pulau Cinta tourist attraction on the people's economy. This study used a survey method and the respondents were 100 tourists, 42 business owners (business units), and 47 workers. Data collection was carried out using questionnaires and retrieval of documentation. The results showed that the types of businesses found in the Pulau Cinta tourist attraction were places to eat and drink, banana boat rentals, ATV motorbikes, and ornamental boats, the impact that occurred changes the livelihoods of the surrounding community due to new jobs in the tourism sector and increases in income, the multiple impact value shows that the Keynesian income multiplier is 1.17, the type I income multiplier ratio is 1.83 and the type II income multiplier ratio is 1.91 which means that Pulau Cinta tourism has an economic impact on the community, especially on people's income local Teluk Kenidai.